POST-TRAUMATIC STRESS DISORDER IN MILITARY SERVICEMEN DURING MILITARY OPERATIONS - Лузік, Ельвіра; Швидченко, Вікторія; Грибун, Нікіта (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2024)
The objective of the article. The article is devoted to highlighting the problem of overcoming post-traumatic stress disorder among military personnel as a result of experiencing severe traumatic events. It has been theoretically proven that military operations on the territory of Ukraine, where both civilians and military personnel are exposed to traumatic events associated with a threat to life, physiological injuries, and psychological disorders, affect the mental health of the nation. As a result, these events lead to post-traumatic stress disorder, which, in terms of its structure and treatment, is a complex mental illness with consequences. That is why the problem identified in the article is that people’s reactions to traumatic events have a wide spectrum that is subject to analysis and classification, and the source of the traumatic event requires, in turn, appropriate methodological research. For specialists, scientists and the state, the task is to develop effective mechanisms for implementing appropriate mechanisms and measures in working with military personnel and civilians with their personal conditions related to the prevention and elimination of existing post-traumatic stress disorder. Researchers and practicing specialists in this field see the solution to the problem in developing effective mechanisms and implementing appropriate methods and technologies for working with military personnel and civilians in need of prevention or elimination of post-traumatic stress disorder. The key goal of the article is the theoretical justification and practical implementation of the features of overcoming post-traumatic stress disorder among military personnel and the development of effective methods of their psychological rehabilitation and social adaptation after returning from the combat zone. The following methods were used for the study: theoretical analysis of scientific research and works on post-traumatic stress disorder; systematization of empirical material to form the validity of the goal with an orientation to personally oriented approaches to the problem of PTSD research. The result of the study is a theoretical generalization of the processed data on the problem of post-traumatic stress disorder; interpretation of the concept of "post-traumatic stress disorder (PTSD)" and its definition in the case of military operations; a number of effective methods have been developed to maintain general combat readiness and social integration of military personnel after their return to civilian life, which will contribute to improving the mental health of the individual. Conclusions. Post-traumatic stress disorder (PTSD) is a complex mental disorder that occurs as a result of experiencing extreme stressful situations, such as life-threatening situations, physical violence, or other traumatic events. Post-traumatic stress disorder (PTSD) significantly affects the emotional and cognitive spheres, manifesting itself through flashbacks, nightmares, increased vigilance, and avoidance of situations reminiscent of the traumatic experience, especially in the context of war. Due to the complex psychological nature of PTSD, its treatment requires a comprehensive approach that combines therapeutic and medical methods, including cognitive-behavioral therapy and pharmacotherapy. The Recovery Through Inner Strength program plays a key role in the effective rehabilitation and support of military personnel, helping to prevent the negative consequences of PTSD and promoting the social integration of those affected. Key words: post-traumatic stress disorder (PTSD); disorder as a result of psychological trauma; psychological support mechanisms; military personnel; social integration of military personnel into civilian life.